PRIORITY DIRECTIONS FOR IMPROVING THE QUALITY OF HIGHER EDUCATION - Alimova Mavlyuda Shukhratbekovna (Modern American Journals, 2025)
The article analyzes the reforms implemented in Uzbekistan’s higher education system, modern approaches to improving the quality of education, and opportunities for enhancing the educational process based on international experience. Key priorities are identified, including the integration of innovative pedagogical technologies, digital education opportunities, and international cooperation. Based on scientific analysis, concrete recommendations for improving higher education quality are provided.
Keywords: Higher education, education quality, innovative pedagogy, digital education, international cooperation, distance learning, academic mobility.